P355 Preferences and satisfaction of IBD patients in whom the adalimumab regimen was changed from 40 mg weekly to 80 mg every other week: the ADASCAL study. (27th May 2021) - Taxonera Samso, C; Martínez-Montiel, P; Barreiro-De-Acosta, M; Vera, I; Lorente, R; Vega, P; Diz-Lois, M T; Fuentes Coronel, A M; Pérez Calle, J L; Casis, B; Ferreiro, R; Calvo, M; et al.
Abstract: Background: Adalimumab (ADA) dose escalation from 40 mg SC every other week (EOW) to 40 mg weekly is approved for IBD patients with loss of response. A recently registered device containing 80 mg of ADA will allow an alternative dose escalation regimen with SC doses of 80 mg EOW. The ADASCAL study aimed to evaluate the preferences and satisfaction of patients with modifying the ADA regimen from 40 mg weekly to 80 mg EOW. Methods: This multicentre cross-sectional study included patients with IBD in whom the ADA regimen was changed from 40 mg weekly to 80 mg EOW according to clinical practice. Patients who have received at least 4 doses of 80 mg EOW completed a 4-item self-questionnaire (a Likert-like 5-point scale for preferences, 2 closed questions for convenience, and a 100-point visual analogue scale [VAS] to evaluate patient's preference for weekly or EOW ADA) (Figure 1); and the 14-item Treatment Satisfaction Questionnaire for medication (TSQM 1.4) that covers 4 domains: effectiveness, side effects, convenience, and overall satisfaction. Results: Seventy-seven patients (64 CD, 13 UC; 67.5% men; mean age 48 years, SD 14.1) were included. The overall mean duration of exposure to ADA was 66 months (SD 34), with mean exposure to ADA 40 mg weekly of 40 months (SD 25), and mean exposure to ADA 80 mg EOW of 12 months (SD 5). At the time of the survey, 87.1% of CD patients and all UC patients were in clinical remission (Harvey-Bradshaw index ≤4 for CD, Partial Mayo score ≤1 for UC). According to the results of the questionnaires, 74% of the patients preferred the 80 mg EOW ADA regimen (59.7% had a strong preference and 14.3% had a slight preference) (Figure 1). Patients referred that ADA EOW regimen interferes less with daily activity and with travel plans. Most patients wanted to continue with ADA 80 mg EOW, as reflected by a mean VAS score of 84.7 (SD 24.1), where 0 indicated a choice for weekly ADA, 100 for ADA EOW, and 50 indifferent. Overall, 77% of patients preferred to continue with ADA EOW, 4% with ADA weekly, and 17% were indifferent. Attending physicians also reported a greater preference for the EOW ADA regimen (mean VAS score 93, SD 7.8). The mean global satisfaction according to the TSQM was 84.3% (SD 13.5), where 0 indicated extremely dissatisfied and 100 extremely satisfied. Patients reported very high TSQM scores for individual components: effectiveness 77.6% (SD 16.9), convenience 83.7% (SD 14.5), and side effects 86.1% (SD 23.4). Conclusion: IBD patients in whom the ADA regimen was changed from 40 mg weekly to 80 mg EOW reported a higher preference for the EOW regimen. TSQM results indicated that patients had a high level of satisfaction with the current EOW regimen. Therefore, most patients wanted to continue with ADA 80 mg EOW.